Allergy Burden in Gujarat: A Community Portrait of Adult Experiences - P, Shah Ashka; B, Desai Om; P, Patel Shrujal; H, Dhalani Mayank; K, Patel Anand (Eastern Journal of Medical Sciences, 2025)
Background: Allergies aren’t just a health issue; they disrupt daily life, work, and social interactions. With over a third of adults affected and many unaware of their condition, there’s a pressing need for better diagnosis, education, and environmental policies. Addressing allergies means improving lives, not just treating symptoms. Allergic diseases present a significant public health issue in India. The increasing prevalence is attributed to several factors, including environmental, genetic, and lifestyle-related factors. Objective: This study aimed to determine the prevalence of self-reported allergic conditions among adults in Vadodara, Gujarat, and assess their associations with environmental and demographic factors. Material and Methods: A cross-sectional study was conducted among 474 adults (aged 18–65) using a structured questionnaire based on international health assessment tools. Data on demographics, allergy symptoms, lifestyle factors, and environmental exposures were collected and analyzed. Results: The overall prevalence of allergic conditions was 33.7%, with 161 of the 474 participants affected, with allergic rhinitis (23.2%) being the most common, followed by allergic conjunctivitis (11.6%), skin allergies (11.2%), and food allergies (10.5%) and asthma (7.1%). A positive family history was found to be associated with the development of allergies (OR = 4.69, p < 0.0001), and the prevalence was significantly higher among urban populations (39.5% vs. 24.0%, OR = 1.8, p = 0.019). Conclusion: The research indicates a significant prevalence of allergic conditions in Gujarat adults and demonstrates the role of environmental and lifestyle exposures to allergy. The study shows the importance of public health interventions, pollution control measures, and enhanced healthcare resources.